Interaction of the antiphospholipid syndrome autoantigen beta-2 glycoprotein I with DNA and neutrophil extracellular traps - Kmeťová, Katarína (Clinical immunology (Orlando, Fla.), 2023)
Copyright © 2023 Elsevier Inc. All rights reserved.